The Future of Learning: AI-Powered Personalized Education through Flipped Classroom Instructional Strategy for Primary Students - Hashim, Siti Noor Aneeis; Mahzan, Saifolrudin Khalid; Abbas, Mohd Saleh; Asuhaimi, Farhanin Abdullah; Ab Ghani, Muhamad Amin; Nordin, Mohd Norazmi; Krishnan, Vijayaletchumy (SEEJPH, 2025)
This review explores the integration of Artificial Intelligence (AI) with the flipped classroom instructional strategy for primary students, focusing on personalized learning experiences. AI has the potential to transform traditional education models by allowing real-time data analytics and adaptive learning systems to create individualized learning pathways. By flipping the traditional classroom model—where students engage with new content at home and apply it in the classroom—AI can enhance engagement, support diverse learning styles, and improve academic outcomes. The article synthesizes the latest research and case studies from 2013 to 2024, examining the benefits, challenges, and implications of combining AI and the flipped classroom model for primary education.